Long-term amendment of four different compost types on a loamy silt Cambisol: impact on soil organic matter, nutrients and yields. Issue 5 (16th April 2017) - Lehtinen, Taru; Dersch, Georg; Söllinger, Josef; Baumgarten, Andreas; Schlatter, Norman; Aichberger, Karl; Spiegel, Heide
ABSTRACT: This study investigated the long-term effects of different composts (urban organic waste compost (OWC), green waste compost (GWC), cattle manure compost (MC) and sewage sludge compost (SSC)) compared to mineral fertilisation on a loamy silt Cambisol, after a 7-year start-up period. The compost application rate was 175 kg N ha −1, with 80 kg mineral N ha −1 and without. Soil characteristics (soil organic carbon (SOC), carbon-to-nitrogen (C/N) ratio and soil pH), nutrients (nitrogen (N), phosphorous (P) and potassium (K)) and crop yields were investigated between 1998 and 2012. SOC concentrations were increased by compost applications, being highest in the SSC treatments, as for soil pH. N contents were significantly higher with compost amendments compared to mineral fertilisation. The highest calcium-acetate-lactate (CAL)-extractable P concentrations were measured in the SSC treatments, and the highest CAL-extractable K concentrations in the MC treatments. Yields after compost amendment for winter barley and spring wheat were similar to 40 kg mineral N ha −1 alone, whereas maize had comparable yields to 80 kg mineral N ha −1 alone. We conclude that compost amendment improves soil quality, but that the overall carbon (C) and N cycling merits more detailed investigation.